2022
DOI: 10.1681/asn.2020111638
|View full text |Cite
|
Sign up to set email alerts
|

Roxadustat Versus Epoetin Alfa for Treating Anemia in Patients with Chronic Kidney Disease on Dialysis: Results from the Randomized Phase 3 ROCKIES Study

Abstract: BackgroundConcerns regarding cardiovascular safety with current treatments for anemia in patients with dialysis-dependent (DD)-CKD have encouraged the development of alternatives. Roxadustat, an oral hypoxia-inducible factor prolyl hydroxylase inhibitor, stimulates erythropoiesis by increasing endogenous erythropoietin and iron availability.MethodsIn this open-label phase 3 study, patients with DD-CKD and anemia were randomized 1:1 to oral roxadustat three times weekly or parenteral epoetin alfa per local clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
144
3
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(163 citation statements)
references
References 28 publications
6
144
3
10
Order By: Relevance
“…Taken orally, Roxadustat is associated with more gastrointestinal side effects. Studies from Europe and Asia reported similar points in terms of serious adverse events [ 19 , 21 , 24 ]. In our study, patients on Roxadustat experienced more vomiting and nausea when compared to those on EPO.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Taken orally, Roxadustat is associated with more gastrointestinal side effects. Studies from Europe and Asia reported similar points in terms of serious adverse events [ 19 , 21 , 24 ]. In our study, patients on Roxadustat experienced more vomiting and nausea when compared to those on EPO.…”
Section: Discussionmentioning
confidence: 73%
“…The significant presence of patients on peritoneal dialysis in the Roxadustat group could have affected the mean potassium level of the overall group and consequently explain why we do not find hyperkalemia as an adverse event. Also, hyperkalemia as an adverse effect of Roxadustat has been reported much more in studies that had a placebo as a comparator and in non-dialysis patients [ 21 ]. Patients without any replacement therapy (HD or PD) may experience metabolic acidosis or hyperkaliemia over time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to identify alternative therapeutic approaches. Systemic administration of EPO is used to treat adult anemia and has been discussed as a potential treatment for atrophic AMD due to its neuroprotective effects on the retina [ 7 , 37 ]; however, there are associations between increased serum EPO and severity of CNV in AMD patients [ 9 ]. Furthermore, EPO-induced neural protection and angiogenesis have been demonstrated in experimental models through EPOR-mediated signaling [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a hypoxia-inducible factor prolyl hydroxylase inhibitor, the novel agent roxadustat may increase endogenous erythropoietin concentrations by mediating the hypoxia-inducible factor, which is regulated via the inhibition of certain activated domains, such as pan-prolyl hydroxylase (9). Subsequently, it has been incorporated into the therapeutic regimen for anemia in CKD (10).…”
Section: Introductionmentioning
confidence: 99%